ANALISIS SWOT SEBAGAI ALAT BANTU MANAJEMEN DALAM PERENCANAAN STRATEGI PADA PERGURUAN TINGGI UNIVERSITAS ABDURRACHMAN SALEH SITUBONDO (UNARS) - Ediyanto Ediyanto (Growth, 2017)
The aim of this research is to help University of Abdurrachman Saleh Situbondo to be able to organize strategic planning by identifying strength, weakness, opportunity and threat, so that be able to develop and realize strategic programs and produce human resource and quality system. The research method is used in this research is descriptive qualitative approach paradigm, by using identification tool SWOT. The technique of data collection used by the writer is interview and observation to obtain the required data. The result of research is based on the classification of IFAS and EFAS. Note that the total score of internal strategic factor is 2.625. Whereas, the total score of external strategic factor is 2,380. From the result, university of Abdurrachman Saleh has position in quadrant V, which it is in a good position to take advantage internal strength, and take advantage from external opportunity. Therefore, the appropriate strategy is used by IE Matrix is stability- growth that can be selected between intensive strategy and vertical integration strategy. The strategy be able used is market penetration, product development and market development.